Sequential dosing in chemosensitization: targeting the PI3K/Akt/mTOR pathway in neuroblastoma. - Mike-Andrew Westhoff; Najmeh Faham; Daniela Marx; Lisa Nonnenmacher; Claudia Jennewein; Stefanie Enzenmüller; Patrick Gonzalez; Simone Fulda; Klaus-Michael Debatin (PLoS ONE, 2013)
Breaking resistance to chemotherapy is a major goal of combination therapy in many tumors, including advanced neuroblastoma. We recently demonstrated that increased activity of the PI3K/Akt network is associated with poor prognosis, thus providing an ideal target for chemosensitization. Here we show that targeted therapy using the PI3K/mTOR inhibitor NVP-BEZ235 significantly enhances doxorubicin-induced apoptosis in neuroblastoma cells. Importantly, this increase in apoptosis was dependent on scheduling: while pretreatment with the inhibitor reduced doxorubicin-induced apoptosis, the sensitizing effect in co-treatment could further be increased by delayed addition of the inhibitor post chemotherapy. Desensitization for doxorubicin-induced apoptosis seemed to be mediated by a combination of cell cycle-arrest and autophagy induction, whereas sensitization was found to occur at the level of mitochondria within one hour of NVP-BEZ235 posttreatment, leading to a rapid loss of mitochondrial membrane potential with subsequent cytochrome c release and caspase-3 activation. Within the relevant time span we observed marked alterations in a ∼30 kDa protein associated with mitochondrial proteins and identified it as VDAC1/Porin protein, an integral part of the mitochondrial permeability transition pore complex. VDAC1 is negatively regulated by the PI3K/Akt pathway via GSK3β and inhibition of GSK3β, which is activated when Akt is blocked, ablated the sensitizing effect of NVP-BEZ235 posttreatment. Our findings show that cancer cells can be sensitized for chemotherapy induced cell death - at least in part - by NVP-BEZ235-mediated modulation of VDAC1. More generally, we show data that suggest that sequential dosing, in particular when multiple inhibitors of a single pathway are used in the optimal sequence, has important implications for the general design of combination therapies involving molecular targeted approaches towards the PI3K/Akt/mTOR signaling network.